IMPLEMENTASI PROGRAM KAMPUNG SIAGA BENCANA DI DESA WLAHAR KECAMATAN ADIPALA KABUPATEN CILACAP - Dinatanaya Candra Kinanti; Teta Riasih; Atirista Nainggolan (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2022)
This study aims to obtain an empirical description of: 1) the characteristics of disaster-prone rural communities, 2) ways to provide understanding and awareness to the community about disaster hazards and risks, 3) organizing communities to be trained in disaster preparedness, and 4) preparation of local early warning systems. This research uses a qualitative approach with a descriptive method which is intended to describe how the implementation of the Kampung Siaga Bencana (KSB) program works. Data collection techniques used were in-depth interviews, observation, and documentation studies. Determination of informants was carried out using purposive sampling, namely informants were selected according to predetermined criteria, so that 2 (two) KSB administrators were obtained, 1 (one) Wlahar village apparatus, 1 (one) Wlahar village community figure, and 1 (one) Cilacap Regency Social Service. The results showed that the implementation of the KSB program in Wlahar Village, Adipala District, Cilacap Regency had been carried out. However, these programs have not been implemented optimally due to the lack of active village disaster preparedness institutions (KSB) in Wlahar Village. The characteristics of disaster-prone village communities related to threats, vulnerabilities, and capacities have been identified, but the level of community understanding of disaster hazards and risks is still lacking, because the KSB method of providing education is less varied. Community organizing is still not optimal. Local early warning system preparations have been carried out.